EVOLVING LESSON PLANNING SKILLS: A STUDY OF EFL STUDENTS IN A MICROTEACHING COURSE OF ENGLISH EDUCATION PROGRAM AT UNIVERSITAS CENDERAWASIH - Rommy D.B. Rambet; Adolfina Krisifu; Maximus Nemo; Andri Robert Wally (FKIP Universitas Cenderawasih, 2024)
This study investigates the development of EFL students’ lesson planning skills over the course of a Microteaching class. By analyzing three lesson plans created by 20 participants at different stages of the course, the research reveals significant improvements in key instructional areas, including learning objectives, lesson structure, instructional strategies, engagement, digital tool integration, and assessment methods. Moreover, participants improved lesson planning and objective alignment, though initial lesson coherence and appropriate digital tool selection posed challenges. While engagement strategies advanced, early lessons relied heavily on teacher-led instruction, limiting student interaction. The findings provide insights into how Microteaching facilitates pedagogical skill development and offer recommendations for improving teacher education programs. Key words: Microteaching, EFL Teacher Education, Lesson Planning, Pedagogical Development